Analisis Perkembangan Produksi dan Efisiensi Teknis Komoditas Pangan di Indonesia - Purba, Khairul Fahmi; Intan, Dian Retno; Tafarini, Meitry Firdha; Sari, Yulia; Wardani, Azqia; Yuliani, Maulidia Tri (LPPM Universitas Malikussaleh - Indonesia, 2025)
Food security is a critical concern for Indonesia which is well-known as an agricultural country. The risk of a food crisis can be mitigated through comprehensive assessments of production trends and efficiency analysis of Indonesia’s food crops commodities. This study aims to demonstrate the production trends of Indonesia’s strategic food crops commodities namely paddy, maize, soybean, cassava, and sugarcane. This study also aims to measure the technical efficiency score among the food crop commodities. The research utilized secondary time-series data from 1999 to 2023, comprising agricultural input variables such as land area, fertilizer, agrochemical, and labor, alongside the output of food commodity production. The analytical methods applied were Data Envelopment Analysis (DEA) and descriptive statistics. The results showed that the production of food crops commodities in Indonesia over the past 25 years has been relatively volatile and varied, with most commodities demonstrating adequate satisfying technical efficiency. However, soybean production requires particular attention due to its lower performance in both production volume and technical efficiency. The study also analyzed the agricultural input use trends. The finding highlights an ongoing increase in land area for food crop cultivation through extensification programs. Meanwhile, the use of chemical fertilizers and agrochemicals has continued to rise. On the other hands, the use of organic fertilizers has declined, raising concerns about sustainability. These findings are expected to inform policymakers in designing and implementing agricultural development programs to achieve national food self-sufficiency.